Cell delivery systems using alginate : carrageenan hydrogel beads and fibers for regenerative medicine applications - Popa, Elena Geta (2011)
The present work was focused on the development and characterization of new hydrogel systems based on natural origin polymers, namely, alginate and carrageenan, into different formats and with adequate properties to sustain the viability of encapsulated cells, envisioning their application as cell delivery vehicles for tissue regeneration. Different formulations of alginate and carrageenan hydrogels and different processing parameters were considered to determine the best conditions required to achieve the most adequate response in terms of the mechanical stability, cell viability, and functionality of the developed systems. The morphology, size, and structure of the hydrogels and their degradation behavior and mechanical properties were evaluated during this study. In addition to cytotoxicity studies, preliminary experiments were carried out to investigate the ability of alginate−carrageenan beads/fibers to encapsulate chondrocytes. The results obtained indicated that the different formulations, both in the form of beads and fibers, have considerable potential as cell-carrier materials for cell delivery in tissue engineering/ regenerative medicine applications.